2014
DOI: 10.1167/iovs.14-15843
|View full text |Cite
|
Sign up to set email alerts
|

Relative Roles of Luminance and Fixation in Inducing Dissociated Vertical Divergence

Abstract: Dissociated vertical divergence is mediated primarily by changes in fixation and only to a minor degree by binocular luminance disparity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…It has been previously suggested that DVD may be quantified using the simultaneous prism cover test,(Velez, 1988) although this test would fail to detect any latent component. In other studies, DVD has been measured using video-oculography,(Ghadban et al, 2015) but such testing methods are often not readily available to the clinician. We recommend a standardized PUCT as the current method of choice for quantifying the magnitude of DVD in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously suggested that DVD may be quantified using the simultaneous prism cover test,(Velez, 1988) although this test would fail to detect any latent component. In other studies, DVD has been measured using video-oculography,(Ghadban et al, 2015) but such testing methods are often not readily available to the clinician. We recommend a standardized PUCT as the current method of choice for quantifying the magnitude of DVD in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Dissociated congenital strabismus manifest slow, variable, and asymmetric movements that can be vertical called Dissociated Vertical Deviation (DVD) or horizontal movements, known as Dissociated Horizontal Deviation (DHD) [26]. Because dissociated movements are manifested by the patients when one eye is occluded or when fixation changes [27], it is believed that the asymmetric input exacerbates them [28], [29]. Dissociated movements have a poor prognosis in the sense of leading to unsatisfactory results [30], [31], compared to non-dissociated forms.…”
Section: A Congenital Strabismus and Pupillometrymentioning
confidence: 99%
“…Pathogenesis of childhood concomitant strabismus is still little known, though various studies have investigated its primum movens postulating new hypotheses [1], and several possible risk factors have been identified [2,3]. In the onset and development of infantile concomitant strabismus there is a sharing of both hereditary and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…It arises from firing of the reticular formation in the brainstem during the waking state. Excessive esotonus somehow induced by unbalanced visual input at an early age has been hypothesized to be a cause of ET or a factor opposing to divergence in Intermittent Exotropia (IXT) [1,5,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%